Sustainable Transportation Managing in University Campuses: The Case of Middle East Technical University - Mustafa Verşan Kök; Adem Kalinli; Altan İlkuçan (Universitas Diponegoro, 2022)
As the level of income of countries rises, sustainability-related issues are improved in general; however, problems regarding the increase in the amount of waste and carbon emissions worsen. The increasing level of wealth in both developing and developed countries, as well as cultural transformations that encourage the use of personal vehicles, threaten sustainability on a global scale. Generally, higher education institutions are places of great mobility thanks to their students, personnel, and visitors. For this reason, creating eco-friendly ways of transportation in these places is one of the most important aspects of having sustainable campuses. The reason why it is crucial is that creating a livable environment by providing sustainable transportation alternatives on campuses leads students to potentially continue with these practices in their lives afterward. Although there are various widely accepted practices of managing sustainable transportation implemented in higher education institutions, it is of great importance for these institutions to conduct a comprehensive situation analysis first so that their sustainable transportation policies can be shaped correctly. In this way, it can be possible for the universities to evaluate their current situations thoroughly and thus implement their own practices in accordance with their conditions. This study endeavors to examine the issue of eco-friendly transportation for sustainable campuses, evaluate the practices of Middle East Technical University in this respect, and raise suggestions for higher education institutions.Keyword: Sustainability, Transportation Management, University Campus